THE INTERNATIONAL LIBRARY OF AFRICAN MUSIC - Tracey, Andrew (International Library of African Music, 1987)
On the 30th May 1986, Article No. 10253 in the Government Gazette stated that the Section 21 non-profit company known as International Library of African Music (ILAM) had been deregistered. At that moment the long months of negotiation between ILAM and Rhodes University came to an end and ILAM found a permanent home. Dennis Etheredge who, as Secretary of the Chairman's Fund of Anglo-American Corporation, and then as Chairman of the Chamber of Mines, had frequently been asked to tide the ILAM over to better times, proposed that the long-term answer to the continuity of both ILAM and African music studies in South Africa was to bring it permanently under the wing of a university. The ILAM finally moved to Grahamstown in 1978, after the death of Dr. Hugh Tracey the previous year, and the building was officially opened by Dennis Etheredge to the sound of a full Chopi xylophone orchestra directed by Venancio Mbande
Keywords: African Music